Pengaruh Pengembangan Karier, Disiplin Kerja, dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan pada PT Murni Konstruksi Indonesia Palu - Meilani, Tita; Muttaqin, Ridlwan (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
The purpose of this research is to find out how career development, work discipline, and the physical work environment influence the performance of PT Murni Konstruksi Indonesia Palu employees. Multiple linear regression analysis was used, and the study population consisted of 30 employees. Employee performance is a dependent variable, and career development, work discipline, and physical work environment are independent variables. Observations and questionnaires were used to collect data. Various statistical techniques, such as partial hypothesis testing, simultaneous analysis, and coefficient of determination, are included in the data. Research findings show that employees' performance is positively and significantly influenced by career development, work discipline, and physical work environment. Apart from that, these three variables simultaneously positively and significantly influence employees' performance.